2013
DOI: 10.1021/ja404616c
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Cationic Vinyl-Addition and Ring-Opening Copolymerization Using B(C6F5)3 as a Catalyst: Copolymerization of Vinyl Ethers and Isobutylene Oxide via Crossover Propagation Reactions

Abstract: Alkyl vinyl ethers and isobutylene oxide were concurrently copolymerized through cationic vinyl addition and ring opening using B(C6F5)3 as a catalyst. NMR analyses and acid hydrolysis of the products demonstrated that the copolymerization successfully proceeded through crossover reactions between vinyl and cyclic monomers to yield multiblock-like copolymers. Appropriate catalyst and monomer combinations with suitable reactivities were key for copolymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
93
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(96 citation statements)
references
References 21 publications
2
93
1
Order By: Relevance
“…Therefore, the hydrolysis experiment confirmed that crossover reactions between styrene and β‐BL occurred. The existence of non‐degradable segment in copolymer chains is also reported by Aoshima and coworkers in the copolymerization of vinyl ethers with isobutylene oxide and aldehydes . The long sequence of non‐degradable segment was attributed to the reactivity difference between monomers.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Therefore, the hydrolysis experiment confirmed that crossover reactions between styrene and β‐BL occurred. The existence of non‐degradable segment in copolymer chains is also reported by Aoshima and coworkers in the copolymerization of vinyl ethers with isobutylene oxide and aldehydes . The long sequence of non‐degradable segment was attributed to the reactivity difference between monomers.…”
Section: Resultssupporting
confidence: 82%
“…Although the hybrid copolymerization of polar vinyl monomers with cyclic esters have been reported based on anionic or cationic polymerization mechanism, the copolymerization of cyclic esters with non‐polar vinyl monomers remains a challenge because of the dramatically different monomer reactivities. Styrene‐based polymers are a major class of commercial polymers, which also contribute for white waste .…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…For example, Saegusa et al found that oxazolines and maleimides could undergo hybrid copolymerization via a zwitterionic mechanism . Aoshima’s group reported a series of hybrid copolymerizations between vinyl ethers and oxetane monomers . Polymerizations of this type rely on a long‐lived cationic propagating species and are based on a cationic mechanism.…”
Section: Introductionmentioning
confidence: 99%